Molecular Characterization of Vitellogenin and Its Receptor in Sogatella furcifera, and Their Function in Oocyte Maturation - Hu, Kui; Tian, Ping; Tang, Yan; Yang, Lu; Qiu, Lin; He, Hualiang; Ding, Wenbing; Li, Zhongcai; Li, Youzhi (Frontiers in Physiology, 2019)
The yolk protein precursor, vitellogenin (Vg), provides nutrition for embryonic development whereas the vitellogenin receptor (VgR) is responsible for the uptake of yolk protein by maturing oocytes. These two proteins are key reproduction-related proteins in insects. We cloned and characterized Vg and VgR genes in Sogatella furcifera, and investigated their function in oocyte maturation. Cloned SfVg and SfVgR have open reading frames of 6 114 and 5 796 bp, encoding 2 037 and 1 931 amino acid residues, respectively. Structural analysis indicates that SfVg has the three conserved LPD_N, DUF1943 and VWFD domains, SfVgR contains all conservative motifs of the LDLR superfamily. Both genes were highly expressed in adult females; SfVg was most highly expressed in the fat body whereas SfVgR was mainly expressed in the ovary. Knockdown of either gene reduced yolk protein deposition in oocytes and arrested oocyte maturation. However, silencing one of these two genes did not affect the transcript level of the other. These results demonstrate the role of SfVgR in transporting SfVg into oocytes. Both SfVg and SfVgR are essential for oocyte maturation in S. furcifera and both genes could potentially be targeted as means of controlling this pest.